2004
DOI: 10.1111/j.1083-4389.2004.00194.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Peptic Ulcers in Patients Following Successful Helicobacter pylori Eradication: A Multicenter Study of 4940 Patients

Abstract: Curative treatment of H. pylori infection is useful in preventing ulcer recurrence. Gastric ulcer is more likely to relapse than duodenal ulcer. Recurrent ulcer tended to recur at the site of the original ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
3
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(62 citation statements)
references
References 26 publications
1
57
3
1
Order By: Relevance
“…Furthermore, over 4,000 multicenter studies spent 4 years in Japan indicated that the recurrence ratio of gastric ulcer or duodenal ulcer is only 1-2 % per annum after eradication [47]. We found NSAID meditation records and habit of smoking or drinking alcohol more significantly in the recurrence cases of gastric ulcer; 93.1 % of gastric ulcer recurred as gastric ulcer, and all duodenal ulcers recurred as duodenal ulcers.…”
Section: Ulcer Recurrence After Eradicationmentioning
confidence: 67%
See 1 more Smart Citation
“…Furthermore, over 4,000 multicenter studies spent 4 years in Japan indicated that the recurrence ratio of gastric ulcer or duodenal ulcer is only 1-2 % per annum after eradication [47]. We found NSAID meditation records and habit of smoking or drinking alcohol more significantly in the recurrence cases of gastric ulcer; 93.1 % of gastric ulcer recurred as gastric ulcer, and all duodenal ulcers recurred as duodenal ulcers.…”
Section: Ulcer Recurrence After Eradicationmentioning
confidence: 67%
“…In contrast, in the unsuccessfully eradicated group, it showed a significantly higher rate of each of 65 and 85 %. Also, over 4,000 multicenter studies spent 4 years in Japan [47] indicated that the recurrence ratio of gastric ulcer or duodenal ulcer is only 1-2 % per annum after eradication. Therefore, we should conduct an infection diagnosis on the cases of gastric or duodenal ulcer which have neither active hemorrhage nor are associated with NSAID, and also we should conduct eradication treatment on the cases infected by H. pylori.…”
Section: Prevention Of Ulcer Recurrencementioning
confidence: 99%
“…Helicobacter pylori is a gram-negative bacterium known as a common pathogen associated with atrophic and metaplastic changes in the stomach, and peptic ulcer disease [1][2][3]. Antibiotic treatment for H. pylori commonly includes a combination of proton pump inhibitors (PPIs) and one or several antibacterial agents such as amoxicillin, clarithromycin, and metronidazole [4].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] H. Pylorinin duodenal ülser oluşumunda ve nükste etkili olmadığı-na yönelik görüşler de bildirilmiştir. [12][13][14] Kalach ve ark.nın Avrupa çapında yaptıkları 694 olgunun incelendiği ileriye yönelik çok merkezli bir çalışmada H. Pylori enfeksiyonunun, peptik ülser gelişmiş olan çocukların %27'sinde görüldüğü bildirilmiştir. [15] Bu çalışmada duodenal ülser nedeniyle perforasyon oluşmuş olguların hiçbirinde yüksek gastrin düzeyi saptanmadı ancak yine de ameliyat sonrası dönemde minimum altı hafta proton pompa inhibitörü kullandık.…”
Section: Discussionunclassified